Antimicrobial Susceptibility, Biotypes and Phylotypes of Clinical Cutibacterium (Formerly Propionibacterium) acnes Strains Isolated from Acne Patients: An Observational Study - Nanxue Zhang; Ruoyue Yuan; Kevin Z. Xin; Zhong Lu; Ying Ma (Adis, Springer Healthcare, 2019)
Abstract Introduction The aim of this study was to investigate the distribution of antimicrobial susceptibility, biotypes and phylotypes of clinical Cutibacterium acnes (C. acnes, formerly Propionibacterium acnes) isolates as well as the relationship among demographic factors, C. acnes biotypes and phylotypes. Methods Cutibacterium acnes was collected from the skin lesions of acne patients who visited the dermatologic department of Huashan Hospital in Shanghai from October 2016 to March 2017. The agar dilution method was conducted to determine the minimum inhibitory concentrations (MICs) of C. acnes, the fermentation test to identify biotypes and then multiplex touchdown polymerase chain reaction (PCR) to identify phylotypes. Results Of the 63 C. acnes strains we isolated, 18 (28.6%), 31 (49.2%) and 4 (6.3%) strains were resistant to clindamycin, erythromycin and moxifloxacin, respectively; no strains were resistant to tetracycline, minocycline, fusidic acid or β-lactam, while metronidazole was completely resisted; 3 strains showed multidrug resistance (MDR). Biotype III (BIII) was the major biotype (50.8%) followed by BI and BV (both 15.9%), BII (12.7%) and lastly BIV (4.8%). IA1 was the predominant phylotype (71.4%) followed by IA2 (19.0%), II (4.8%), IB (3.2%) and IC (1.6%), while III was not detected. Significant differences were observed in the severity of disease: different degrees of acne severity reflected different biotype and phylotype distributions, and the biotype distribution of mild acne was different from that of moderate acne; the phylotype distribution of moderate acne varies from that of severe acne, too. Additionally, there was no significant difference in the distribution of biotypes or phylotypes between resistant and susceptible strains. Conclusion Erythromycin and clindamycin resistances are the most common in clinical C. acnes strains; BIII is the predominant biotype and IA1 is the major phylotype of C. acnes, which are mainly related to disease severity.